Melt‐Extrusion‐Based Additive Manufacturing of Transparent Fused Silica Glass. Issue 23 (20th October 2021) - Mader, Markus; Hambitzer, Leonhard; Schlautmann, Phillip; Jenne, Sophie; Greiner, Christian; Hirth, Florian; Helmer, Dorothea; Kotz‐Helmer, Frederik; Rapp, Bastian E.
Abstract: In recent years, additive manufacturing (AM) of glass has attracted great interest in academia and industry, yet it is still mostly limited to liquid nanocomposite‐based approaches for stereolithography, two‐photon polymerization, or direct ink writing. Melt‐extrusion‐based processes, such as fused deposition modeling (FDM), which will allow facile manufacturing of large thin‐walled components or simple multimaterial printing processes, are so far inaccessible for AM of transparent fused silica glass. Here, melt‐extrusion‐based AM of transparent fused silica is introduced by FDM and fused feedstock deposition (FFD) using thermoplastic silica nanocomposites that are converted to transparent glass using debinding and sintering. This will enable printing of previously inaccessible glass structures like high‐aspect‐ratio (>480) vessels with wall thicknesses down to 250 µm, delicate parts including overhanging features using polymer support structures, as well as dual extrusion for multicolored glasses. Abstract : Thermoplastic silica nanocomposites allow additive manufacturing of transparent fused silica glass via melt‐extrusion‐based processes like fused deposition modeling and fused feedstock deposition followed by a subsequent sintering process. This enables the manufacturing of transparent high‐aspect‐ratio glass structures with intricate features, complex 3D glass components, as well as multicomponent glasses.